Activation of Glutamate Transport Increases Arteriole Diameter in vivo: Implications for Neurovascular Coupling - Jackson, Joshua G.; Krizman, Elizabeth; Takano, Hajime; Lee, Meredith; Choi, Grace H.; Putt, Mary E.; Robinson, Michael B. (Frontiers in Cellular Neuroscience, 2022)
In order to meet the energetic demands of cell-to-cell signaling, increases in local neuronal signaling are matched by coordinated increase in local blood flow, termed neurovascular coupling. Multiple different signals from neurons, astrocytes, and pericytes contribute to this control of blood flow. Previously, several groups demonstrated that inhibition/ablation of glutamate transporters attenuates the neurovascular response. However, it was not determined if glutamate transporter activation was sufficient to increase blood flow. Here, we used multiphoton imaging to monitor the diameter of fluorescently labeled cortical arterioles in anesthetized C57/B6J mice. We delivered vehicle, glutamate transporter substrates, or a combination of a glutamate transporter substrate with various pharmacologic agents via a glass micropipette while simultaneously visualizing changes in arteriole diameter. We developed a novel image analysis method to automate the measurement of arteriole diameter in these time-lapse analyses. Using this workflow, we first conducted pilot experiments with L-glutamate, D-aspartate, and L-threo-hydroxyaspartate (L-THA) as proof of concept. We subsequently focally applied the selective glutamate transport substrate L-THA (applied at concentrations that do not activate glutamate receptors). We found that L-THA evoked a significantly larger dilation than that observed with focal saline application. This response was blocked by co-application of the potent glutamate transport inhibitor, L-(2S,3S)-3-[3-[4-(trifluoromethyl)-benzoylamino]benzyloxy]-aspartate (TFB-TBOA). Conversely, we were unable to demonstrate a reduction of this effect through co-application of a cocktail of glutamate and GABA receptor antagonists. These studies provide the first direct evidence that activation of glutamate transport is sufficient to increase arteriole diameter. We explored potential downstream mechanisms mediating this transporter-mediated dilation by using a Ca2+ chelator or inhibitors of reversed-mode Na+/Ca2+ exchange, nitric oxide synthetase, or cyclo-oxygenase. The estimated effects and confidence intervals suggested some form of inhibition for a number of these inhibitors. Limitations to our study design prevented definitive conclusions with respect to these downstream inhibitors; these limitations are discussed along with possible next steps. Understanding the mechanisms that control blood flow are important because changes in blood flow/energy supply are implicated in several neurodegenerative disorders and are used as a surrogate measure of neuronal activity in widely used techniques such as functional magnetic resonance imaging (fMRI).